Treatment of non-small cell lung cancer with gefitinib ('lressa', ZD1839): The Greek experience with a compassionate-use program - Razis, E.; Skarlos, D.; Briasoulis, E.; Dimopoulos, M.; Fountzilas, G.; Lambropoulos, S.; Rigatos, S.; Kopterides, P.; Efstathiou, H.; Tzamakou, E.; Bakoyannis, C.; Pectasides, D.; et al. (Anti-Cancer Drugs, 2005)
This is a retrospective analysis of 150 patients with advanced non-small cell lung cancer who had failed prior treatment or were unfit for chemotherapy and were treated with oral gefitinib ('lressa', ZD1839; AstraZeneca) 250 mg/day. Thirty-two patients who received gefitinib for 3 weeks or less were not included in the analysis. For the remaining 118 evaluable patients, the mean age was 63.1 years; most patients had received prior chemotherapy (97.5%), Eastern Cooperative Oncology Group performance status scores 0-2 (97.4%) and stage IV disease (64.4%). The majority were symptomatic (84.6%). Disease control was observed in 30 patients (25.4%), of whom five had a partial response and 25 had stable disease; 18 (15.3%) were not evaluable. Median duration of treatment was 29.9 weeks in responding patients and 11.5 in patients with progressive disease (p<0.0001). Median overall survival was 7.3 months (15.2 months for disease control) and median progression-free survival was 3.2 months. Gefitinib was well tolerated, with grade 3/4 skin rash and diarrhea seen in 2.5 and 4.2% of patients, respectively. Clinical benefit was evaluated using questionnaires before and following treatment with gefitinib. In 82 patients with completed questionnaires, evaluation revealed symptom improvement in 40.1% and improvement in general feeling in 31.4%. Epidermal growth factor receptor (EGFR) analysis found that efficacy did not correlate with tumor EGFR overexpression. Therefore, in this retrospective analysis, gefitinib treatment provided disease control in 25% of patients who derived significant palliative benefit. © 2005 Lippincott Williams & Wilkins.
Keywords: Clinical benefit; Epidermal growth factor receptor; Expanded access program; Gefitinib; Non-small cell lung cancer